A COMPARATIVE STUDY BETWEEN USING VIDEO AND AUDITORY AS MULTIMEDIA-BASED LEARNING STRATEGIES IN STUDENTS' LISTENING COMPREHENSION AT ELEVENTH GRADE IN SMAN 2 KOTA SERANG (A TRUE-EXPERIMENTAL RESEARCH) - Annisa Laila Cahyani; Abdul Muin; Kheryadi, Kheryadi (Sindoro: Cendikia Pendidikan, 2024)
This study explores the comparative efficacy of video-based and audio-based strategies in enhancing listening comprehension among eleventh-grade students at SMAN 2 Kota Serang. Through a true experimental design, data were gathered from two groups, one exposed to video-based instruction and the other to audio-based instruction. Analysis reveals a significant difference in listening comprehension performance, with the video-based approach yielding superior outcomes. These findings underscore the importance of multimedia integration, particularly leveraging visual aids, in optimizing students' comprehension skills. Educational practitioners can use these insights to tailor instructional methods, fostering more effective learning environments that cater to diverse student needs. This research contributes to understanding the role of multimedia strategies in language education, offering valuable implications for pedagogical practices aimed at enhancing listening comprehension proficiency.